Perlindungan Hukum Bagi Penerima Manfaat Dana Pensiun Yang Mengalami Keterlambatan Pembayaran - Rachel, Leviana; Maengkom, Yuliana Risna; Napitupulu , Diana R.W. (Jurnal De Jure Muhammadiyah Cirebon, 2025)
Pension beneficiaries are parties who have the right to receive timely payments as stipulated in the applicable regulations. Delays in the implementation of pension payments can have adverse consequences for beneficiaries, not only in terms of material losses, but also non-material losses, such as disruption in the fulfillment of daily financial needs that are mandatory. This research focuses on analyzing the forms of legal protection that have been available to pension fund beneficiaries who face the problem of late payments, as well as assessing the extent of the effectiveness of existing regulations in ensuring the fulfillment of their rights. The methods applied in this study include a normative legal approach combined with real case studies as concrete illustrations. A comprehensive analysis was carried out on various sets of laws and regulations related to pension funds, ranging from laws, government regulations, to policies issued by pension fund management institutions. Based on the results of the study, it was found that although the legal framework for the payment of pension funds has been designed, the application of sanctions against late payments still has significant weaknesses. Furthermore, the existing dispute resolution mechanisms show a tendency to take a long time, which ultimately worsens the conditions of the beneficiaries. From these findings, the study recommends revisions to existing regulations, including the drafting of additional rules that are stricter on the provision of sanctions, as well as efforts to improve efficiency in dispute resolution mechanisms. With stronger legal protections, it is hoped that the rights of pension fund beneficiaries can be better guaranteed, while the risk of late payments can be minimized in the future.  Keywords: Legal protection, Pension fund recipients, Laws and Regulations, Government Policy, Right to timely payment.